PERANCANGAN SISTEM INFORMASI PENGELOLAAN ZAKAT DAN INFAQ MENGGUNAKAN METODE EXTREME PROGRAMMING BERBASIS WEB DI MUSHOLLA AL-MUHAJIRIN - Allan Firmansyah (PT Triputra Sejahtera Prima, 2023)
Zakat is a worship that concerns property that has a social function. Every Muslim is obliged to pay zakat. As one of the intermediaries, Musholla Al-Muhajirin can collect data and distribute it to those in need. In this implementation, zakat management is still running manually, where in the application of this management system there are several things that become a problem, namely the effectiveness of the zakat management process and the efficiency of using paper, the current form of zakat management reports is still in handwriting which can make it difficult in the data search process, and the possibility of missing data. With the reasons above, the authors try to provide an alternative solution to the problem by creating a zakat management system application that will record incoming zakat and then make it systematic and computerized so that it will eliminate the process of recording teacher attendance which has been running manually at Al-Muhajirin Mosque. and also using the programming method will reduce the input error rate in the zakat management process. In this paper, the stages of work will also be explained, starting from the process of analysis, planning, construction using a web-based application and MySQL as its database, to the implementation stage using the spiral method with engineering notation and an object-oriented UML (Unified Modeling Language) approach.